Manufacturing Practice : Introduction To Sheet Metal Shop-1 - Sankara Rao, Dr. Lakkoju (Main Workshop, Indian Institute of Technology (BHU), Varanasi, 2016)
This video explains the different tools used in the sheet metal shop and shows the step by step procedure to prepare the galvanized iron sheet tray.
Keywords: Sheet metal; galvanization